Implementation of intentionally structured psychosocial through folk games and traditional sports in elementary school students - Rekha Ratri Julianti; Adang Suherman; Amung Ma'mun; Dian Budiana; Eka Fitri Novita Sari; Mochamad Ridwan; Rifqi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to examine the impact of intentionally structured psychosocial programs through folk games and traditional sports on elementary school students. Psychosocial factors influence individual thoughts and behaviors, and traditional games and sports are known for their character-building and cultural values. The research used a pretest-posttest group design with a quantitative approach, focusing on 5th-grade students from Sumur Batu 06 Public Elementary School in Central Jakarta. The primary instrument was the Questionnaire on Psychosocial Adjustment Needs of Grade 7 Students, covering social cognitive, socio-emotional, social, teacher-student, peer, parent, and sibling relationships. The study followed Kendellen's model, which emphasizes focusing on one psychosocial component per lesson, introducing it at the lesson's beginning, teaching it throughout the lesson, and reviewing it at the end. Data analysis was conducted using SPSS version 22, including only students with at least 80% attendance who completed both pre-tests and post-tests. Normality tests confirmed that data from both integrated and non-integrated groups were normally distributed, while homogeneity tests showed that the samples were from a homogeneous population. Paired sample t-tests revealed significant improvements in psychosocial outcomes for both groups, with the integrated group showing a t-value of 7.453 (Sig. 0.000) and the non-integrated group a t-value of 5.121 (Sig. 0.000). These results indicate a significant positive effect of psychosocially integrated traditional games and sports on the psychosocial development of elementary school students.